Euthanasia, Female Genital Mutilation, Children with Disabilities: A Review on Societal Issues and Their Scientific Implications - , Gabriel Odeh Ankeli (Archives of Current Research International, 2019)
This paper reviewed some societal challenges, their causes, possible scientific solutions to them and the controversies arising from each of them. Three societal problems were identified which are; Euthanasia, Female Genital Mutilation (FGM) and Children with Disabilities (CWDs). The different types of Euthanasia were identified as the active and passive ethanasia respectively also the FGM was discussed under three main types, namely; clitoridectomy, excision, infibulation and others, while the CWDs was also discussed, the causes and challenges they go through such as discrimination and institutional and environmental challenges. In each case their causes, effects and scientific solutions were proffered.